Balancing assessment load and effectiveness in medical education during the pandemic: Students’ insights - Cristóvão, Helena Landim Gonçalves; Cristóvão, Paula Helena Gonçalves; Cristóvão, André Bavaresco Gonçalves; Cristóvão, Nathalia Bavaresco Gonçalves; Massonetto, Júlio César; Santos, Emerson Roberto dos; Menezes, João Daniel de Souza; Silva, Matheus Querino da; Oliani, Denise Cristina Mós Vaz; Brienze, Vânia Maria Sabadoto; Lima, Alba Regina de Abreu; André, Júlio César (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The COVID-19 pandemic has significantly impacted medical education, forcing institutions to adapt to remote learning and assessment methods. This study aimed to explore medical students’ perceptions of their assessment load, quality, and impact on learning during the pandemic at a university in São Paulo, Brazil. Methods: A cross-sectional study with a quantitative approach and qualitative perspective was conducted. Ninety-one sixth-semester undergraduate medical students completed an online questionnaire assessing their perceptions of three assessment tools (online TBL, guided study, and pre-post-test) using Likert scales. Descriptive statistics and Spearman correlation coefficients were used for data analysis. Results: Guided study was the most effective tool in promoting student engagement and learning, while online TBL was perceived as the least useful. The assessment load was considered manageable by most participants, and no correlation was found between effort dedicated to assessment tools and perceived study load. A positive correlation was observed between the usefulness of tools in conducting learning and the development of ethical concepts. Conclusions: The findings highlight the importance of adapting assessment strategies to the remote learning environment, considering students’ preferences and needs. Further research is needed on the long-term impact of remote learning and assessment on medical students’ professional and ethical development